Endoscopic transsphenoidal removal of neoplasms of the chiasmal-sellar region in children - A. V. Burmistrova; V. J. Сherebillo; W. A. Khachatryan (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to analyze the results of endoscopic transsphenoidal removal of neoplasms of the chiasmalsellar region in children.MATERIALS AND METHODS. We studied 23 patients aged 3 to 17 years who underwent endoscopic transsphenoidal removal of neoplasms of the chiasmal-sellar region. Neurological, ophthalmological, endocrine disorders and otorhinolaryngological pathology were evaluated. Neuroimaging data (MRI and CT), results of laboratory tests were studied. In addition, the analysis of surgical treatment including intraoperative and early postoperative complications was performed.RESULTS. In 39.1 % of cases, neoplasms of supraparainfracellar localization were diagnosed. In 34.8 % of patients, the size of the neoplasms did not exceed 2 cm. In 1 patient, the volume of neoplasm was 53.7 cm3. According to the type of pneumatization, the sellar type prevailed. Сonch type was observed in 1 child. Hemostatic material «Surgicel Fibrillar» was used more often (86.9 %). Plastic surgery of the skull defect was carried out on a floor-by-floor basis with «Tachocomb» plates (62.5 %). Total tumor removal was achieved in 75 % of children. The majority of neoplasms were represented by craniopharyngioma – 30.43 %. In the early postoperative period, there was a significant regression of neurological disorders – by 69.6 %, as well as ophthalmological – by 34.8 % and endocrine – by 37.8 %. There were no cases of nasal liquorrhea and epistaxis in children.CONCLUSION. Our study demonstrated the success of removing neoplasms in children from 3 years old, regardless of the size of the nasal cavity and pneumatization of the sphenoid sinus. It is possible to use endoscopic transsphenoidal access in children to remove the neoplasms of the chiasmal-sellar region of more than 5 cm, since the risk of intra – and postoperative complications is minimized.